Preparation method and application of (NixCo0.5-x) 0.85 Se / MoSe2 / RGO ternary complex
By preparing (NixCo0.5-x) 0.85Se/MoSe2/RGO ternary composite, the problems of low specific capacity and insufficient cycle stability of metal selenide and molybdenum diselenide electrode materials in the prior art are solved, and high Supercapacitor with energy density and excellent cycle performance, simple process and low cost.
Patent Information
- Application Number
- CN202411413856.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-01-10
AI Technical Summary
The existing metal selenide and molybdenum diselenide have low specific capacity as supercapacitor electrode materials, poor cycle stability, and large room for performance improvement.
Using a preparation method of (NixCo0.5-x) 0.85Se/MoSe2/RGO ternary complex, the ternary complex was obtained through hydrothermal reaction and subsequent treatment, and applied to the electrode preparation and performance evaluation of supercapacitors. .
It improves the specific capacity and cycling performance of supercapacitors, is suitable for high energy density applications, is simple in preparation process and low in cost, and is suitable for large-scale production.
Smart Images

Figure CN119296987A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of preparation of energy storage materials and energy storage performance evaluation, and specifically to a (Ni x Co 0.5-x ) 0.85 Preparation method and application of Se / MoSe2 / RGO ternary composite. Background Art
[0002] In recent years, carbon-based materials such as graphene, carbon / graphene aerogels, carbon spheres, and carbon nanotubes have been found to have good electrical conductivity, and researchers have widely used them in supercapacitors. By combining carbon-based materials with MoSe2, its conductivity can be improved, thereby improving its electrochemical performance. The existing technology synthesizes MoSe2 / G nanocomposites by a simple solvothermal method. At a current density of 1A / g, the specific capacitance of the MoSe2 / G electrode is 945F / g. MoSe2 / G is used as the positive electrode and activated carbon is used as the negative electrode to assemble a MoSe2 / G / / AC asymmetric capacitor. At a current density of 1A / g, the specific capacitance of the MoSe2 / G / / AC capacitor is 75F / g. The prior art synthesized MoSe2 / RGO nanosheets by a hydrothermal method. At a current density of 5A / g, the maximum specific capacitance of the MoSe2 / RGO nanosheet electrode was 211F / g. After 10,000 constant current charge and discharge cycles, the capacitance retention rate was 180%. The combined effect of pseudocapacitance and double-layer capacitance led to the enhancement of specific capacitance. The prior art also successfully grew MoSe2-rGO nanocomposites on the surface of rGO by a hydrothermal method, and studied the morphology and electrochemical properties of the MoSe2-rGO nanocomposites by changing the graphene content. The research results show that when the graphene content is 25mg, the electrochemical performance of the MoSe2-rGO-25 electrode is the best. At a current density of 1A / g, the specific capacity of the MoSe2-rGO-25 electrode is 814.4F / g. Based on the three-electrode research, the MoSe2-rGO-25 electrode was assembled into a supercapacitor. At a current density of 1A / g, the specific capacitance of the supercapacitor was 215.7F / g; at a current density of 10A / g, the capacitance retention rate of the capacitor was 81.7% after 5000 cycles. Metal selenides and molybdenum diselenide have attracted great attention as supercapacitor electrode materials, but their specific capacities are relatively low, the cycle stability is not ideal, and there is still a lot of room for improvement in performance. Summary of the invention
[0003] The object of the present invention is to provide a (Ni x Co 0.5-x ) 0.85The preparation method and application of Se / MoSe2 / RGO ternary composite are used to solve the problems existing in the prior art mentioned in the above background technology.
[0004] To achieve the above object, the present invention provides the following technical solutions:
[0005] A (Ni x Co 0.5-x ) 0.85 The preparation method of Se / MoSe2 / RGO ternary composite comprises the following steps:
[0006] S1: ultrasonically disperse GO in water, add sodium molybdate and polyvinyl pyrrolidone, and stir to obtain dispersion A;
[0007] S2: dissolving selenium powder in hydrazine hydrate and stirring to form a uniform selenization solution B;
[0008] S3: Slowly add dispersion A into selenization solution B, stir evenly, transfer to a hydrothermal reactor, cool to room temperature after hydrothermal reaction, collect black precipitate, wash and freeze-dry to obtain MoSe2 / RGO;
[0009] S4: MoSe2 / RGO is ultrasonically dispersed in water, and a certain proportion of nickel nitrate and cobalt nitrate are dissolved in the MoSe2 / RGO dispersion to form a precursor C;
[0010] S5: dissolving a certain amount of selenium powder in a reducing solution to obtain a selenized solution D;
[0011] S6: Slowly add the precursor C into the selenization solution D and stir evenly to obtain the reaction solution E;
[0012] S7: The reaction solution E is subjected to hydrothermal reaction under certain conditions, and then centrifuged, washed, and freeze-dried to obtain (Ni x Co 0.5-x ) 0.85 Se / MoSe2 / RGO ternary composite.
[0013] Preferably, the concentration of the GO dispersion in S1 is 1-3 g / L.
[0014] Preferably, the ratio of selenium powder to hydrazine hydrate in S2 is 1:2-1:5 mol / L.
[0015] Preferably, the hydrothermal reaction conditions in S3 are keeping warm at 200° C. for 12 hours, and the detergents are ethanol and water.
[0016] Preferably, the molar ratio of nickel nitrate to cobalt nitrate in S4 is 1:4-4:1.
[0017] Preferably, the hydrothermal reaction conditions in S7 are keeping warm at 120° C. for 6 hours and freeze-drying time for 30 hours.
[0018] The present invention also provides a (Ni x Co 0.5-x ) 0.85 Application of Se / MoSe2 / RGO ternary composite x Co 0.5-x ) 0.85 Se / MoSe2 / RGO ternary composite is applied in supercapacitors.
[0019] Preferably, the method includes electrode preparation and performance evaluation for supercapacitors, and the specific method is as follows:
[0020] (1) Electrode preparation: x Co 0.5-x ) 0.85 Se / MoSe2 / RGO ternary composite, acetylene black and PVDF were mixed and ground in N-methylpyrrolidone in a certain proportion, and then the slurry was evenly coated on nickel foam, vacuum dried, and then pressed into a thin sheet electrode;
[0021] (2) Electrochemical performance evaluation: x Co 0.5-x ) 0.85 Se / MoSe2 / RGO electrode was used as the working electrode, Hg / HgO electrode as the reference electrode, and Pt sheet electrode as the counter electrode to form a three-electrode system. The electrochemical properties of the electrodes were studied using cyclic voltammetry and constant current charge-discharge techniques.
[0022] (3) Assembly and energy storage performance evaluation of hybrid capacitors: (Ni x Co 0.5-x ) 0.85 A hybrid supercapacitor was assembled with Se / MoSe2 / RGO electrode as the positive electrode, activated carbon electrode as the negative electrode, and potassium hydroxide solution as the electrolyte. The energy storage performance of the capacitor was studied by cyclic voltammetry, constant current charge and discharge, and electrochemical impedance spectroscopy.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] 1. The (Ni x Co 0.5-x ) 0.85 Compared with the single metal selenide / MoSe2 / RGO composite (Ni 0.85 Se / MoSe2 / RGO or Co 0.85The specific capacity of Se / MoSe2 / RGO) is improved, and it can be applied to supercapacitors with high energy density.
[0025] 2. The (Ni 0.2 Co 0.3 ) 0.85 Se / MoSe2 / RGO ternary composites assembled with (Ni 0.2 Co 0.3 ) 0.85 Se / MoSe2 / RGO / / AC hybrid capacitors exhibit excellent cycling performance.
[0026] 3. The preparation process of the present invention is simple, easy to operate, has low requirements on preparation conditions, does not require complex equipment, has low preparation cost, and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 For Examples 1-4 and Comparative Examples 1-2 prepared (Ni x Co 0.5-x ) 0.85 XRD pattern of Se / MoSe2 / RGO.
[0028] Figure 2 For Examples 1-4 and Comparative Examples 1-2 prepared (Ni x Co 0.5-x ) 0.85 CV curves of Se / MoSe2 / RGO ternary composite electrode at a scan rate of 60 mV / s.
[0029] Figure 3 For Examples 1-4 and Comparative Examples 1-2 prepared (Ni x Co 0.5-x ) 0.85 GCD curve of Se / MoSe2 / RGO ternary composite electrode at current density of 0.5 A / g.
[0030] Figure 4 For Examples 1-4 and Comparative Examples 1-2 prepared (Ni x Co 0.5-x ) 0.85 Specific capacitance of Se / MoSe2 / RGO electrode at different current densities.
[0031] Figure 5 The (Ni prepared in Example 1 0.2 Co 0.3 ) 0.85 Se / MoSe2 / RGO ternary composite (Ni 0.2 Co 0.3 ) 0.85CV plots of Se / MoSe2 / RGO / / AC hybrid capacitor at different scan rates.
[0032] Figure 6 The (Ni prepared in Example 1 0.2 Co 0.3 ) 0.85 Se / MoSe2 / RGO ternary composite (Ni 0.2 Co 0.3 ) 0.85 GCD curves of Se / MoSe2 / RGO / / AC hybrid capacitors at current densities of 0.5–10 A / g.
[0033] Figure 7 The (Ni prepared in Example 1 0.2 Co 0.3 ) 0.85 Se / MoSe2 / RGO ternary composite (Ni 0.2 Co 0.3 ) 0.85 Lagung plot of Se / MoSe2 / RGO / / AC hybrid capacitor.
[0034] Figure 8 The (Ni prepared in Example 1 0.2 Co 0.3 ) 0.85 Se / MoSe2 / RGO ternary composite (Ni 0.2 Co 0.3 ) 0.85 Cycling performance diagram of Se / MoSe2 / RGO / / AC hybrid capacitor.
[0035] Fig. 9 The (Ni prepared in Example 1 0.2 Co 0.3 ) 0.85 Se / MoSe2 / RGO ternary composite (Ni 0.2 Co 0.3 ) 0.85 Phase angle versus frequency plot of Se / MoSe2 / RGO / / AC hybrid capacitor. DETAILED DESCRIPTION
[0036] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further explained below in conjunction with specific implementation methods.
[0037] See also Figure 1-8 , the present invention provides the following technical solutions:
[0038] Example 1
[0039] A (Nix Co 0.5-x ) 0.85 The preparation method of Se / MoSe2 / RGO ternary composite comprises the following steps:
[0040] S1: Weigh 50.0 mg GO and disperse it in 25.0 mL water by ultrasonic. Add 0.5 mmol sodium molybdate dihydrate and 0.2 g polyvinyl pyrrolidone and stir to obtain dispersion A.
[0041] S2: Dissolve 1.0 mmol of selenium powder in 5.0 mL of hydrazine hydrate and stir to form a uniform selenide solution B;
[0042] S3: Slowly add dispersion A into selenization solution B, stir evenly, transfer to a 50.0 mL hydrothermal reactor, perform hydrothermal reaction at 200 °C, and keep warm for 12 h. After cooling to room temperature, collect the black precipitate, wash with water and ethanol, and then freeze-dry for 30 h to obtain MoSe2 / RGO.
[0043] S4: 30.0 mg MoSe2 / RGO was weighed and ultrasonically dispersed in 25.0 mL water, and 0.2 mmol nickel nitrate hexahydrate and 0.3 mmol cobalt nitrate hexahydrate were dissolved in the MoSe2 / RGO dispersion to form precursor C;
[0044] S5: Dissolve 0.5 mmol of selenium powder in 2.0 mL of hydrazine hydrate to obtain selenide solution D;
[0045] S6: Slowly add the precursor C into the selenization solution D and stir evenly to obtain the reaction solution E;
[0046] S7: The reaction solution E was transferred to a 50.0 mL lined autoclave, placed in an oven, and reacted at 120°C for 6 h. After cooling, the reaction solution was centrifuged, washed with water and ethanol, and freeze-dried for 30 h to obtain (Ni 0.2 Co 0.3 ) 0.85 Se / MoSe2 / RGO ternary composite.
[0047] The steps of Example 2-4 and Comparative Example 1-2 are the same as those of Example 1, but the ingredients are different, as shown in the following table:
[0048]
[0049] Evaluation of electrochemical activity and energy storage performance
[0050] The (Ni x Co 1-x ) 0.85The Se / MoSe2 / RGO ternary composite was made into a test electrode. First, the three-electrode method was used to test (Ni x Co 1-x ) 0.85 Electrochemical activity of Se / MoSe2 / RGO electrode. Then activated carbon was used as negative electrode, (Ni 0.2 Co 0.3 ) 0.85 Se / MoSe2 / RGO electrode is the positive electrode, assembled (Ni 0.2 Co 0.3 ) 0.85 Se / MoSe2 / RGO / / AC hybrid capacitor, using CV, GCD and EIS to study the energy storage performance of the capacitor. The specific steps are as follows:
[0051] (1) Electrode preparation: First, weigh (Ni x Co 1-x ) 0.85 Se / MoSe2 / RGO, acetylene black and PVDF were added with an appropriate amount of NMP to prepare a slurry, and then the slurry was coated on the nickel foam, which was placed in a vacuum drying oven and dried at 80°C for 12h. After drying, it was pressed into a thin sheet as a working electrode;
[0052] (2) Electrochemical performance evaluation: x Co 1-x ) 0.85 Se / MoSe2 / RGO electrode was used as the working electrode, Hg / HgO electrode was used as the reference electrode, and Pt sheet electrode was used as the counter electrode to build a three-electrode system. The electrochemical activity of the electrodes was studied using CV and GCD techniques.
[0053] (3) Assembly and energy storage performance evaluation of hybrid capacitors: (Ni 0.2 Co 0.3 ) 0.85 Se / MoSe2 / RGO electrode is the positive electrode, AC electrode is the negative electrode, and the assembled (Ni 0.2 Co 0.3 ) 0.85 Se / MoSe2 / RGO / / AC hybrid capacitor, the energy storage performance of the capacitor was studied using techniques such as CV, GCD and EIS.
[0054] Figure 1 The (Ni x Co 0.5-x ) 0.85 XRD pattern of Se / MoSe2 / RGO ternary composite. As can be seen from the figure, Figure 1The diffraction peaks at 33.3°, 44.7°, 50.6°, 60.4°, 61.9°, 69.9° and 71.3° are consistent with Ni 0.85 Se(JCPDS No.18-0888) and Co 0.85 Se (JCPDS No.52-1008); the diffraction peaks at 29.7°, 61.6° and 69.9° correspond to the (110), (220) and (310) crystal planes of carbon (JCPDS No.54-0501), respectively. In addition, with the increase of Co content, the intensity of the diffraction peak gradually weakens, indicating that with the increase of Co, (Ni x Co 0.5-x ) 0.85 The crystallinity of Se / MoSe2 / RGO sample gradually deteriorates.
[0055] Figure 2 For Examples 1-4 and Comparative Examples 1-2 prepared (Ni x Co 0.5-x ) 0.85 Se / MoSe2 / RGO series samples at 60mVs -1 CV curves in the range of 0-0.6V at the scan rate. It can be seen from the figure that there are obvious oxidation / reduction peaks on each curve. In addition, (Ni 0.2 Co 0.3 ) 0.85 The response current of Se / MoSe2 / RGO electrode is the highest. 0.2 Co 0.3 ) 0.85 The area enclosed by the CV curve of Se / MoSe2 / RGO electrode is larger than that of single metal selenide / MoSe2 / RGO (Ni 0.85 Se / MoSe2 / RGO and Co 0.85 Se / MoSe2 / RGO) and other Ni / Co ratios (Ni x Co 0.5-x ) 0.85 Se / MoSe2 / RGO composites show that (Ni x Co 0.5-x ) 0.85 The synergistic effects among Se nanoparticles, Ni-Co intermetallics, and MoSe2 and RGO enhance the electrochemical activity.
[0056] Figure 3 For Examples 1-4 and Comparative Examples 1-2 prepared (Ni x Co 0.5-x ) 0.85 GCD curve of Se / MoSe2 / RGO electrode at 0.5A / g current density. Figure 3It can be seen that each curve has a discharge platform. x Co 0.5-x ) 0.85 The discharge time of Se / MoSe2 / RGO electrode is significantly longer than that of Ni 0.85 Se / MoSe2 / RGO and Co 0.85 Se / MoSe2 / RGO, indicating that the energy storage performance of bimetallic selenide / MoSe2 / RGO is significantly better than that of single metal selenide / MoSe2 / RGO. When Ni / Co=0.2 / 0.3, (Ni 0.2 Co 0.3 ) 0.85 The discharge time of Se / MoSe2 / RGO electrode is the longest, indicating that (Ni 0.2 Co 0.3 ) 0.85 Se / MoSe2 / RGO electrode has large energy storage performance.
[0057] Figure 4 For Examples 1-4 and Comparative Examples 1-2 prepared (Ni x Co 0.5-x ) 0.85 The specific capacitance of Se / MoSe2 / RGO electrode at different current densities. As the current density increases, the specific capacitance decreases. At the same current density, (Ni 0.2 Co 0.3 ) 0.85 Se / MoSe2 / RGO electrode exhibits the largest specific capacitance. At a current density of 0.5 A / g, (Ni 0.2 Co 0.3 ) 0.85 The specific capacity of Se / MoSe2 / RGO electrode is 410.4C / g, which is higher than that of single metal selenide / MoSe2 / RGO (Ni 0.85 Se / MoSe2 / RGO and Co 0.85 Se / MoSe2 / RGO) and other Ni / Co ratios (Ni x Co 0.5-x ) 0.85 The specific capacity of Se / MoSe2 / RGO electrode is further explained by the fact that (Ni x Co 0.5-x ) 0.85 The synergistic effect between Se nanoparticles, Ni-Co metal and MoSe2 and RGO was achieved, which improved the (Ni 0.2 Co 0.3 ) 0.85 Electrochemical energy storage performance of Se / MoSe2 / RGO.
[0058] Figure 5 The (Ni prepared in Example 1 0.2 Co 0.3 ) 0.85 Se / MoSe2 / RGO ternary composites assembled with (Ni 0.2 Co 0.3 ) 0.85 CV curve of Se / MoSe2 / RGO / / AC hybrid supercapacitor at 2-100mV / s. 0.2 Co 0.3 ) 0.85 The maximum operating voltage of Se / MoSe2 / RGO / / AC hybrid capacitor can be extended to 1.6V. -1 At the scanning rate, each CV curve has a pair of oxidation / reduction peaks, indicating that (Ni 0.2 Co 0.3 ) 0.85 Se / MoSe2 / RGO / / AC capacitors rely not only on double layers but also on Faraday reactions to store charge. As the scan rate increases, the area enclosed by the CV curve continues to increase, but the shape of the CV curve remains basically unchanged, which means that (Ni 0.8 Co 0.2 ) 0.85 Se / N-MoSe2 / / AC capacitors have high rate performance and good reversibility.
[0059] Figure 6 The (Ni prepared in Example 1 0.2 Co 0.3 ) 0.85 Se / MoSe2 / RGO ternary composites assembled with (Ni 0.2 Co 0.3 ) 0.85 GCD curves of Se / MoSe2 / RGO / / AC hybrid capacitors at current densities of 0.5-10A / g. There is an inconspicuous voltage platform on the discharge curve, indicating that there is a Faraday reaction involved in the constant current discharge process. At current densities of 0.5, 1, 2, 4, 6, 8, and 10A / g, the specific capacitance of the capacitor is 41.8, 39.0, 35.8, 32.0, 29.3, 27.6, and 25.7F / g, respectively.
[0060] Figure 7 The (Ni prepared in Example 1 0.2 Co 0.3 ) 0.85 Se / MoSe2 / RGO ternary composites assembled with (Ni 0.2 Co 0.3 ) 0.85Lagung diagram of Se / MoSe2 / RGO / / AC hybrid capacitor. At a specific power of 400 W kg -1 The device can provide 14.9Wh kg -1 The specific energy.
[0061] Figure 8 The (Ni prepared in Example 1 0.2 Co 0.3 ) 0.85 Se / MoSe2 / RGO ternary composites assembled with (Ni 0.2 Co 0.3 ) 0.85 Cyclic performance diagram of Se / MoSe2 / RGO / / AC hybrid capacitor. At a current density of 3A / g, after 30,000 cycles, (Ni 0.2 Co 0.3 ) 0.85 The capacity retention rate of Se / MoSe2 / RGO / / AC is 113.6%, indicating that the capacitor has excellent cycling stability.
[0062] Fig. 9 The (Ni prepared in Example 1 0.2 Co 0.3 ) 0.85 Se / MoSe2 / RGO ternary composites assembled with (Ni 0.2 Co 0.3 ) 0.85 Phase angle and frequency relationship diagram of Se / MoSe2 / RGO / / AC hybrid capacitor. The relaxation time τ0 is 0.2s, indicating that (Ni 0.2 Co 0.3 ) 0.85 The response time of Se / MoSe2 / RGO electrode is very short, which can realize fast charge and discharge, further proving that (Ni 0.2 Co 0.3 ) 0.85 Fast electrochemical response of Se / MoSe2 / RGO / / AC capacitor.
[0063] The metal selenide / molybdenum diselenide / graphene ternary composite constructed by the present invention can not only increase the redox reaction sites, but also improve the conductivity and stability of the material. The advantages of developing a reasonable bimetallic selenide / molybdenum diselenide / / graphene ternary composite and applying it to supercapacitors are as follows: (1) MoSe2 with a large interlayer spacing is conducive to the diffusion of electrolyte ions and can provide more abundant active sites, which can accelerate the Faraday redox kinetics; (2) Coupling (Ni on MoSe2 and RGO substrate) x Co 0.5-x ) 0.85Se can prevent the stacking of layered MoSe2 and RGO, thereby maximizing the number of active sites in the composite. The introduction of RGO can also increase the conductivity and stability of the material; (3) Construction (Ni x Co 0.5-x ) 0.85 Se / MoSe2 / RGO ternary composite can not only play the role of (Ni x Co 0.5-x ) 0.85 The synergistic effect between Se and MoSe2 and RGO can also play a synergistic effect between Ni-Co, thereby enhancing the kinetics of the Faradaic redox reaction and thus improving the electrochemical performance.
[0064] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A (Ni x Co 0.5-x ) 0.85 The method for preparing the Se / MoSe2 / RGO ternary composite is characterized in that: The steps include: S1: ultrasonically disperse GO in water, add sodium molybdate and polyvinyl pyrrolidone, and stir to obtain dispersion A; S2: dissolving selenium powder in hydrazine hydrate and stirring to form a uniform selenization solution B; S3: Slowly add dispersion A into selenization solution B, stir evenly, transfer to a hydrothermal reactor, cool to room temperature after hydrothermal reaction, collect black precipitate, wash and freeze-dry to obtain MoSe2 / RGO; S4: MoSe2 / RGO is ultrasonically dispersed in water, and a certain proportion of nickel nitrate and cobalt nitrate are dissolved in the MoSe2 / RGO dispersion to form a precursor C; S5: dissolving a certain amount of selenium powder in a reducing solution to obtain a selenized solution D; S6: Slowly add the precursor C into the selenization solution D and stir evenly to obtain the reaction solution E; S7: The reaction solution E is subjected to hydrothermal reaction under certain conditions, and then centrifuged, washed, and freeze-dried to obtain (Ni x Co 0.5-x ) 0.85 Se / MoSe2 / RGO ternary composite.
2. According to claim 1, a (Ni x Co 0.5-x ) 0.85 The preparation method of Se / MoSe2 / RGO ternary composite is characterized by: The concentration of the GO dispersion in S1 is 1-3 g / L.
3. A (Ni according to claim 1 x Co 0.5-x ) 0.85 The preparation method of Se / MoSe2 / RGO ternary composite is characterized by: The ratio of selenium powder to hydrazine hydrate in S2 is 1:2-1:5 mol / L.
4. A (Ni according to claim 1 x Co 0.5-x ) 0.85 The preparation method of Se / MoSe2 / RGO ternary composite is characterized by: The hydrothermal reaction conditions in S3 are 200° C. for 12 hours, and the detergents are ethanol and water.
5. A (Ni according to claim 1 x Co 0.5-x ) 0.85 The preparation method of Se / MoSe2 / RGO ternary composite is characterized by: The molar ratio of nickel nitrate to cobalt nitrate in S4 is 1:4-4:
1.
6. A (Ni according to claim 1 x Co 0.5-x ) 0.85 The preparation method of Se / MoSe2 / RGO ternary composite is characterized by: The hydrothermal reaction conditions in S7 are: keeping warm at 120° C. for 6 hours, and freeze drying time is 30 hours.
7. A method of preparing (Ni) by the method according to any one of claims 1 to 6 x Co 0.5-x ) 0.85 The application of Se / MoSe2 / RGO ternary composite is characterized by: Will (Ni x Co 0.5-x ) 0.85 Se / MoSe2 / RGO ternary composite is applied in supercapacitors.
8. A (Ni according to claim 7 x Co 0.5-x ) 0.85 The application of Se / MoSe2 / RGO ternary composite includes electrode preparation and performance evaluation for supercapacitors. The specific methods are as follows: (1) Electrode preparation: x Co 0.5-x ) 0.85 Se / MoSe2 / RGO ternary composite, acetylene black and PVDF were mixed and ground in N-methylpyrrolidone in a certain proportion, and then the slurry was evenly coated on nickel foam, vacuum dried, and then pressed into a thin sheet electrode; (2) Electrochemical performance evaluation: x Co 0.5-x ) 0.85 Se / MoSe2 / RGO electrode was used as the working electrode, Hg / HgO electrode as the reference electrode, and Pt sheet electrode as the counter electrode to form a three-electrode system. The electrochemical properties of the electrodes were studied using cyclic voltammetry and constant current charge-discharge techniques. (3) Assembly and energy storage performance evaluation of hybrid capacitors: (Ni x Co 0.5-x ) 0.85 Se / MoSe2 / RGO electrode was used as the positive electrode, activated carbon electrode as the negative electrode, and potassium hydroxide solution as the electrolyte to assemble a hybrid supercapacitor. The energy storage performance of the capacitor was studied by cyclic voltammetry, constant current charge and discharge, and electrochemical impedance spectroscopy.